+0  
 
+1
169
2
avatar+73 

(x^5-x^3-x^2+3)+(x^4-2x^3-2x^2+4x-3)

 Sep 8, 2018
 #1
avatar+27578 
+1

Combine the terms that are of the same order.  The order is given by the power to which the x’s are raised. So, here, we have:

 

Order      Terms

5.             x^5

4.             x^4

3.             -x^3-2x^3 → -3x^3

2.             -x^2-2x^2 → -3x^3

1.             4x

0.             3-3 → 0

 

Result:  x^5 + x^4 - 3x^3 - 3x^2 + 4x

 Sep 8, 2018
 #2
avatar+73 
0

Thanks

BabyChimChim  Sep 8, 2018

35 Online Users

avatar
avatar
avatar
avatar
avatar